THE BLOOD-BRAIN BARRIER AS A PHYSIOLOGICAL AND TOXICOLOGICAL SYSTEM OF BRAIN PROTECTION: STRUCTURAL AND FUNCTIONAL ORGANIZATION, TRANSPORT MECHANISMS, AND THE SIGNIFICANCE OF DYSFUNCTION IN CENTRAL NERVOUS SYSTEM DISORDERS - Kalyuzhin, Alexander Sergeevich; Belchiuk, Mikhail Petrovich; Dushkina, Maria Andreevna; Mashdieva, Mayagozel Sakhipovna (Medicine in Kuzbass, 2026)
This review systematizes data on the structural and functional organization of the blood-brain barrier, its barrier-related and transport-metabolic mechanisms, universal mechanisms of dysfunction, and the significance of impaired barrier integrity for xenobiotic penetration, the development of neurotoxic effects, and changes in the sensitivity of the central nervous system to chemical and pharmacological exposures. The methodological basis of the study was an analysis of more than 200 literature sources. The search was performed using a specifically developed set of keywords to ensure maximum relevance of the selected publications. PubMed and Scopus were used as the main information resources, which made it possible to cover publications on the problem under consideration published between 2021 and 2026. The analysis showed that the structural integrity of the neurovascular unit, the functional state of nutrient transport systems and ABC-dependent efflux, as well as inflammatory and proteolytic damage to intercellular junctions and the basement membrane, are key determinants of blood-brain barrier status, xenobiotic penetration into the brain, the severity of neurotoxic effects, and changes in CNS sensitivity to chemical and pharmacological exposures.